Radiation for hematologic malignancies: from cell killing to immune cell priming - Dabaja, Bouthaina; Spiotto, Michael (Frontiers in Oncology, 2023)
Over the past half-century, the role of radiotherapy has been revolutionized, in part, by a shift from intent to directly kill cancer cells to the goal of priming anti-tumor immune responses that attack both irradiated and non-irradiated tumors. Stimulation of anti-tumor immunity depends on the interplay between radiation, the tumor microenvironment, and the host immune system, which is a burgeoning concept in cancer immunology (1). While the interplay of radiotherapy and the immune system has been primarily studied in solid tumors, we are beginning to understand this interplay in hematological malignancies. The intent of this review is to lead readers through some of the important recent advances in immunotherapy and adoptive cell therapy, highlighting the best available evidence in support of incorporating radiation therapy and immunotherapy into the treatment of hematological malignancies. Evidence is presented regarding how radiation therapy ‘converses’ with the immune system to stimulate and enhance anti-tumor immune responses. This pro-immunogenic role of radiotherapy can be combined with monoclonal antibodies, cytokines, and/or other immunostimulatory agents to enhance the regression of hematological malignancies. Furthermore, we will discuss how radiotherapy facilitates the effectiveness of cellular immunotherapies by acting as a “bridge” that facilitates CAR T cell engraftment and activity. These initial studies suggest radiotherapy may help catalyze a shift from using chemotherapy-intensive treatment to treatment that is “chemo-free” by combining with immunotherapy to target both the radiated and non-irradiated disease sites. This “journey” has opened the door for novel uses of radiotherapy in hematological malignancies due to its ability to prime anti-tumor immune responses which can augment immunotherapy and adoptive cell-based therapy.